2019
DOI: 10.1111/1744-7941.12244
|View full text |Cite
|
Sign up to set email alerts
|

Is workplace bullying always perceived harmful? The cognitive appraisal theory of stress perspective

Abstract: The present study expands the literature on bullying by unveiling why and when bullying might produce positive outcomes. Employing the cognitive appraisal theory of stress and coping, we hypothesize eustress as an important mechanism through which bullying might enhance the victim's job performance, career success, and creativity. Moreover, we hypothesized psychological capital as a moderator in the workplace bullying-eustress relationship. We collected temporally segregated field data at three time intervals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 79 publications
1
29
1
Order By: Relevance
“…Workplace bullying has emerged as one of the grave issues plaguing every occupation and industry worldwide with far-fetched consequences for its victims (Einarsen et al, 2003;Fontes et al, 2019;Naseer et al, 2018). Past research identifies workplace bullying as a highly prevalent phenomenon in developing countries like Pakistan (e.g., Majeed & Naseer, 2019;Naseer & Raja, 2019;Raja et al, 2018) with nurses being the most vulnerable targets (Islam et al, 2019;Sarwar et al, 2019). In particular the health care industry in a developing country like Pakistan holds immense importance for examining how and when nurses experience of workplace bullying might trigger deviant work behaviors (Sarwar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Workplace bullying has emerged as one of the grave issues plaguing every occupation and industry worldwide with far-fetched consequences for its victims (Einarsen et al, 2003;Fontes et al, 2019;Naseer et al, 2018). Past research identifies workplace bullying as a highly prevalent phenomenon in developing countries like Pakistan (e.g., Majeed & Naseer, 2019;Naseer & Raja, 2019;Raja et al, 2018) with nurses being the most vulnerable targets (Islam et al, 2019;Sarwar et al, 2019). In particular the health care industry in a developing country like Pakistan holds immense importance for examining how and when nurses experience of workplace bullying might trigger deviant work behaviors (Sarwar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary research has found workplace bullying to be a highly prevalent phenomenon in Asian and developing countries like Pakistan (e.g., Majeed & Naseer, 2019;Naseer & Raja, 2019;Naseer et al, 2016;Naseer et al, 2018;Raja, Javed, & Abbas, 2018). In the health sector, nurses are among the most stressed employees in Asian countries like Pakistan due to their nature of work and long working hours (Sarwar, Bashir, & Khan, 2019).…”
mentioning
confidence: 99%
“…This has resulted in some impetuous conclusions referring to workplace bullying as one of the drivers of employee performance in some Eastern contexts. Majeed and Naseer (2019), for instance, suggested that workplace bullying is positively linked to job performance, concluding that workplace bullying creates favorable consequences for the victims in their research context, Pakistan. This signifies the scarcity of relevant research in such contexts and accentuates the need for further research to validate the relevance of the theory in such contexts.…”
Section: Supportive Organizational Climate 1685mentioning
confidence: 99%
“…In this situation, employees tend to lower their self-appraisals and fall into social dilemmas ( Wang et al, 2019 ). As posited by cognitive appraisal theory, negative cognitive evaluation will trigger fluctuations in psychological security and negatively impact behavioral responses ( Majeed and Naseer, 2019 ). When employees are confronted by threatening event, continuing detrimental experience will cause negative psychological feelings or emotions ( Peltokorpi and Ramaswami, 2019 ).…”
Section: Theoretical Basis and Research Hypothesismentioning
confidence: 99%